Establishment of Asia-Pacific Network for Enterovirus Surveillance - Chiu, Mu-Lin; Luo, Shu Ting; Chen, Ya-Yen; Chung, Wan Yu; Duong, Veasna; Dussart, Philippe; Chan, Yoke-Fun; Perera, David; Ooi, Mong How; Thao, Nguyen Thi Thanh; Truong, Huu Khanh; Lee, Min-Shi (Elsevier Ltd., 2019)
Enteroviruses (EV), the major pathogens of hand, foot, and mouth disease (HFMD) and herpangina, affect millions of children each year. Most human enteroviruses cause self-limited infections except polioviruses, enterovirus A71 (EV-A71), enterovirus D68 (EV-D68), and several echoviruses (Echo) and coxsackieviruses (CV). Especially, EV-A71 has repeatedly caused large-scale outbreaks in the Asia-Pacific region since 1997. Some Asian countries have experienced cyclical outbreaks of severe EV-A71 infections and initiated development of EV-A71 vaccines. Five EV-A71 vaccine candidates have been clinically evaluated and three of them were approved for marketing in China. However, none of the China-approved products seek marketing approval in other countries.